2014
DOI: 10.1093/gbe/evu214
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Horizontal Gene Transfer during Staphylococcus aureus Co-colonization In Vivo

Abstract: Staphylococcus aureus is a commensal and major pathogen of humans and animals. Comparative genomics of S. aureus populations suggests that colonization of different host species is associated with carriage of mobile genetic elements (MGE), particularly bacteriophages and plasmids capable of encoding virulence, resistance, and immune evasion pathways. Antimicrobial-resistant S. aureus of livestock are a potential zoonotic threat to human health if they adapt to colonize humans efficiently. We utilized the techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
120
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(127 citation statements)
references
References 54 publications
(91 reference statements)
5
120
1
1
Order By: Relevance
“…Transfer of antimicrobial resistance, however, is highly influenced by the complexity of microflora and its interactions with the host. Moreover, it is presumed that in vitro models underestimate the potential risk for resistance transfer compared to in vivo models [58,59]. Therefore, to appropriately assess the risk for horizontal spread of antimicrobial resistance, many authors have recently performed experimental studies under in vivo conditions.…”
Section: Transmission Of Tetracycline and Mls Resistancementioning
confidence: 99%
“…Transfer of antimicrobial resistance, however, is highly influenced by the complexity of microflora and its interactions with the host. Moreover, it is presumed that in vitro models underestimate the potential risk for resistance transfer compared to in vivo models [58,59]. Therefore, to appropriately assess the risk for horizontal spread of antimicrobial resistance, many authors have recently performed experimental studies under in vivo conditions.…”
Section: Transmission Of Tetracycline and Mls Resistancementioning
confidence: 99%
“…Such selective processes favor the emergence of novel variants, resulting from genetic drift, or migration to heterogeneous environments. Recent studies demonstrated that plasmid transfer occurs in vivo more frequently than in experimental evolution assays (43), and that gradients in populations under selection pressure by diverse antimicrobials favor selection of multidrug resistance (MDR) plasmids (44,45).…”
Section: An Eco-evo Perspective To Analyze Hgt In Firmicutesmentioning
confidence: 99%
“…1B). Besides the potential for programmed ribosomal frameshifting (38) by the 3= poly(A) 5 tract, the two 5= poly(A) 7 tracts occur directly after the initiation codon of orf2 and may add another layer of control over ICE6013 excision.…”
Section: Discussionmentioning
confidence: 99%
“…transducing phages and conjugative plasmids in the horizontal transfer of antimicrobial resistance determinants and virulence factors continue to be documented (3)(4)(5)(6)(7), but little is known about the function of integrative conjugative elements (ICEs) in this species. ICEs, also known as conjugative transposons (Tn's), are maintained primarily by integration into a bacterial chromosome or plasmid and are horizontally transferred by self-encoded conjugation functions (8).…”
mentioning
confidence: 99%